Special Field and Subject Field Lexicography Contributing to Lexicography - Gouws, Rufus H. (Lexikos, 2020)
Restricted dictionaries are fully-fledged dictionaries and their contribution to lexicography should never be underestimated. Because restricted dictionaries often are neglected in lexicographic discussions this article emphasises the significance of their role as members of the lexicographic family. Within a comprehensive dictionary culture the focus should not only be on dictionaries dealing with languages for general purposes but also on dictionaries in which languages for special purposes are treated. This paper firstly offers some terminological clarity and distinguishes between subject field dictionaries and special field dictionaries. The user-perspective is then discussed before it is shown how aspects of a general theory of lexicography also prevail in these dictionaries. This applies among others to the subtypological classification as well as different lexicographic functions. Using a dictionary from each of the categories of subject field and special field dictionaries it is indicated how dictionary structures are employed and further developed in an innovative way. Attention is given to structures like the article structure and the frame structure and to a transtextual approach in monolingual dictionaries with a bilingual dimension. The focus in the discussion of the subject field dictionary is on different aspects of the macrostructure. An explanation is given of double-layered sublemmata and it is shown how integrated macrostructures are employed in this dictionary. It is indicated how this section of the lexicographic practice can enrich the field of metalexicography and dictionary research. Keywords: back matter texts; double-layered sublemmata; first level sublemmata; guiding element; integrated macrostructure; learner's dictionary; partial article stretches; special field dictionary; specialised dictionary; subject field dictionary; sublemmata; transtextual approach; user-perspective